The "Phase Down" of Dental Amalgam Restorations - What are the Criteria for Replacement and Indication? - Diogo de Azevedo Miranda; Lorena Esteves Silveira; Júlia Alves Schirm; Izabella Lucas de Abreu Lima; Flávio Ricardo Manzi (Association of Support to Oral Health Research (APESB), 2024)
Objective: To guide professionals about the criteria for replacing amalgam restorations and inform them about the new guidelines regarding the use/indication of this (amalgam) material after the Minamata Convention - COP-4. Material and Methods: The articles were selected from the databases (PubMed, Scielo, Bireme), and relevant articles on the subject between the years 2003-2021 were selected. Recently, social media have been flooded with dental treatments that aim to perform restorations only with composite resins or other types of esthetic material and completely replace all dental amalgam restorations, irrespective of their time in place, size, and functionality. Results: Although improperly, it has been noted that this information reaches patients, and they are led to believe in the inaccurate data that is passed on, such as, for example, (that amalgam leads to) permanent contamination by mercury, causing systemic problems and the loss of the tooth. Conclusion: The "phase down" of amalgam in research and teaching has previously been observed in several countries worldwide; however, its use is still necessary given particular circumstances, which, theoretically, make it a material with exact indication.